Rethinking the French new right : alternatives to modernity - Bar-On, Tamir (Abingdon, Oxon : Routledge, 2013)
"This book focuses on the philosophy, politics and impact of the 'New Right' which originated in France and has since influenced activism, ideology and policy in a number of European countries"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Conservatism -- France; Right and left (Political science) -- France; Postmodernism -- France; Electronic books